La Recepción del “caso Heidegger” en el campo filosófico español (1988-2008). Una aproximación sociofilosófica - Vázquez García, Francisco (Logos. Anales del Seminario de Metafísica, 2021)
This paper analyzes the controversy over the “Heidegger case”, which arose in Spain as a result of the translation of the book by Víctor Farías, Heidegger y el nazismo. For this, the method of the sociology of philosophy is used. Firstly, it is examined what the emergence of this essay supposed in the context of the readers, predominantly academic, of Heidegger in Spain. Secondly, the Spanish presentation of Farías’s book in 1989 is studied, as if it were a ritual of interaction. Finally, the reactions caused by this diffusion in the world of Spanish experts in Heideggerian philosophy are explored. Since 1989, scholars could no longer stop pronouncing on the links between the ideology and the thought of the German author.